Effects of Veratrilla baillonii Extract on Hepatic Gene Expression Profiles in Response to Aconitum brachypodum-Induced Liver Toxicity in Mice - Li, Jun; Liu, Gang; Ihsan, Awais; Yi, Xuejia; Wang, Da-Gui; Cheng, Han; Muhammad, Azhar; Huang, Xian-Ju (Frontiers in Pharmacology, 2019)
This study was aimed to investigate the hepato-protective effect of water extract of Veratrilla baillonii (WVBF) on acute hepatic toxicity induced in mice treated with Aconitum brachypodum at transcriptome level. The physiological, pathological symptoms and clinical biochemistry parameters were assessed as the markers for hapato toxicity induced by chloroform fraction of Aconitum brachypodum Diels (CFA). Moreover, gene chip technique was used to compare and analyze the gene expression level of WVBF on CFA induced-liver toxicity to identify the potential target of WVBF and CFA on liver. The results showed that WVBF had a significant detoxification effect on CFA-induced acute hepatic toxicity. There were 130 genes down-regulated and 124 genes up-regulated in CFA treated group as compared with normal control group, while there are 67 genes down-regulated and 74 genes up-regulated in WVBF treated group in comparison with CFA treated group. WVBF could attenuate CFA-induced liver damage in mice through regulating oxidative stress, inflammatory injury and cell apoptosis/necrosis pathways. On the other hand, WVBF and CFA may have potential synergetic effects on the target genes of certain diseases such as inflammation, cancer and diabetes.